Superficial Granulomatous Pyoderma Gangrenosum of the Penis: A Case Report - Shyamala S. Gopi; Alan T. Evans; Asif Raza; Derek J. Byrne (The Scientific World Journal)
Classic type of pyoderma gangrenosum (PG) is an uncommon ulceronecrotic cutaneous disease of uncertain aetiology characterised by broad zones of confluent ulceration with violaceous undermined margins. Some 50% of cases are associated with systemic diseases. The superficial granulomatous variant of pyoderma gangrenosum (SGPG) of the external genitalia is extremely rare Patients with this condition develop single or multiple ulcerated skin lesions often with sinus tract formation. The majority of these lesions were found on the trunk and limbs. SGPG is less likely to be associated with underlying disease processes than classic PG. We present a 58 year-old with recalcitrant penile ulceration demonstrated to be SGPG on biopsy. Although rare and poorly recognised, the histological features are sufficiently typical to allow the correct diagnosis to be established.